Effectiveness of a Lock-down to combat COVID-19 using Regression Analysis: A Case Study in India - Jabeena A., Ananya K. R. (International Journal of Advanced Science and Technology, 2020)
Ever since its outbreak in the city of Wuhan in China, COVID-19 has spread around the world at a rapid rate and has now been identified in over 187 countries. To combat the spread of the virus and to isolate the affected, one of the most significant measures taken by various countries around the world is to enforce a complete lock-down across the nation. This paper aims to examine the effectiveness of the one such lock-down enforced in India by the Government on the 24th of March 2020 so as to curb the spread of COVID-19. In order to be able to estimate the effectiveness, an approach of Regression Analysis, which is a sub-branch of Predictive Analytics, has been applied using Python Programming. Upon following this approach, it is observed that the 41-day long lock-down has been highly effective in limiting the total number of COVID-19 positive cases in India.